A Systematic Literature Review on the Effectiveness of GeoGebra in Mathematics Education in the Digital Era - Dini Izdahara; Irvan Irvan (JMEA : Journal of Mathematics Education and Application, 2025)
The integration of digital technologies in mathematics education has become increasingly essential in the digital era. GeoGebra, an interactive mathematics software that combines algebra, geometry, calculus, and statistics, has been widely used to support visual and student-centered learning. This study aims to systematically review the literature on the effectiveness of GeoGebra in mathematics education by analyzing ten peer-reviewed articles published between 2020 and 2025. Using a qualitative descriptive design and systematic literature review method, the selected studies were examined in terms of their educational level, research design, and key findings.The results indicate that GeoGebra significantly enhances students’ conceptual understanding, visualization skills, problem-solving ability, and critical thinking. Moreover, it fosters greater engagement and motivation, particularly when integrated into interactive or constructivist learning settings. However, the review also identified challenges, including teacher readiness, technological infrastructure limitations, and a lack of focus on long-term and non-cognitive outcomes. These findings highlight the need for professional development, pedagogical alignment, and institutional support to optimize GeoGebra’s impact. Overall, GeoGebra holds strong potential as a transformative tool in mathematics instruction, provided its implementation is contextually and pedagogically supported.